Native joint septic arthritis due to Kingella kingae in an adult. (2021) - Chen, Benjamin; Kobayashi, Takaaki; Samra, Hasan; Sekar, Poorani
Abstract: A 65-year-old woman with chronic osteoarthritis of the knees presented with a one-week history of acutely worsening right knee pain and swelling. Arthrocentesis was performed and synovial fluid was indicative of septic arthritis with a negative Gram stain for bacteria. Magnetic Resonance Imaging (MRI) was obtained, revealing a large anterior periarticular abscess with concomitant septic arthritis. Orthopedic surgeons performed urgent incision and drainage of the abscess and washout of the joint. Synovial fluid culture grew Kingella kingae and the patient was treated with four weeks of ceftriaxone with improvement in both clinical symptoms and laboratory values. Kingella kingae is a common cause of pediatric bone and joint infection but remains an exceedingly rare cause of native joint septic arthritis among immunocompetent adults. Kingella spp are largely susceptible to beta-lactam antimicrobials.